Sequences responsible for erythroid and lymphoid leukemia in the long terminal repeats of Friend-mink cell focus-forming and Moloney murine leukemia viruses. - Ishimoto, A (1987)
Despite the high degree of homology (91%) between the nucleotide sequences of the Friend-mink cell focus-forming (MCF) and the Moloney murine leukemia virus (MuLV) genomic long terminal repeats (LTRs), the pathogenicities determined by the LTR sequences of the two viruses are quite different. Friend-MCF MuLV is an erythroid leukemia virus, and Moloney MuLV is a lymphoid leukemia virus. To map the LTR sequences responsible for the different disease specificities, we constructed nine viruses with LTRs recombinant between the Friend-MCF and Moloney MuLVs. Analysis of the leukemia induced with the recombinant viruses showed that a 195-base-pair nucleotide sequence, including a 75-base-pair nucleotide Moloney enhancer, is responsible for the tissue-specific leukemogenicity of Moloney MuLV. However, not only the enhancer but also its downstream sequences appear to be necessary. The Moloney virus enhancer and its downstream sequence exerted a dominant effect over that of the Friend-MCF virus, but the enhancer sequence alone did not. The results that three of the nine recombinant viruses induced both erythroid and lymphoid leukemias supported the hypothesis that multiple viral genetic determinants control both the ability to cause leukemia and the type of leukemia induced.